Essentials of Cross-Cultural Counseling - Leung, Seung-Ming A.; Heppner, P. Paul; Gerstein, Lawrence H.; Gerstein, Lawrence H. (California Sage, 2012)
1. Cross-Cultural Counseling: History, Challenges, and Rationale